A case study of the use of closed circuit television in pre-service teacher education : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Education at Massey University - Chow, Vivian Bee Lian (Massey University, 1974)
Faced with the general problem that there can be 'adoption' of an innovation without its effecting intended changes, the ultimate interest of this study is to make some contributions towards facilitating the implementation of educational innovation. The research involves a case study of the use of closed circuit television in pre-service teacher education as an innovation at the primary division of the Christchurch Teachers' College. It first investigates the severity of problems experienced by regular and non-regular users (or which have led to the non-usage of the innovation). Secondly, it examines the perceived relevance of a list of variables which have been proposed in the literature as influencing the process of change and adoption. Relevance in this study is considered in relation to perceptions of the innovation in an organizational setting. The participants for the study consisted of a defined population of the lecturing staff. This population was selected on the basis that they were full-time, had been on the staff since the introduction of CCTV at the College, and were in regular attendance during the academic terms. Reference to the record of bookings made for use of the equipment revealed data to determine the 28 users as being 13 non-regular and 15 regular users, as distinct from the 15 non-users. These three groups provided the information sought. The information was obtained by means of a semi-structured interview schedule and the use of two separate questionnaires. The first questionnaire was intended to elicit a measure of the extent to which problems were experienced by the regular, non-regular and non-users in relation to CCTV. As a preliminary to this questionnaire, a semi-structured interview was used to identify the difficulties or problems which had been experienced. The list of problems thus obtained formed the context for the questionnaire 1. The second questionnaire contained a list of 25 variables. These represented concepts drawn from the literature where it was suggested that they influenced change and the adoption of an innovation. The participants were required to rate each of the variables on the extent to which they perceived their relevance in relation to the use of CCTV by the staff as a whole. A four-point rating scale (i.e. Great Deal, Much, Not Very Much, and None) was used to obtain the responses in both questionnaires. Descriptive statistical procedures involving means and standard deviations were used to analyze the data, in accordance with the aims of the study. The findings were used to identify the particular problems that could be anticipated so that they might be obviated before they became dominating and hindered adoption. The findings also showed that the problems were on the whole not severe. The variables in Questionnaire 2 generally were seen to be relevant to the case study. Those variables which were relatively outstanding over the others were examined. It appears likely that they have influenced adoption. It was concluded that the problems experienced were of a relatively minor nature. It is suggested that the procedures used in the study do go some way towards identifying both difficulties and facilitating factors. These procedures may be of some use as one aspect of evaluation for change agents, for administrators or for other personnel concerned with change and adoption.
Keywords: Television in education; New Zealand; Teachers -- Training of